Measurement of Hydrogen Diffusion through PVA Hydrogel using Magnetic Resonance Imaging Method in Comparison with Consistency Assessment using Digital Penetrometer - Dita Puspita Sari; Darminto Darminto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2013)
A study of hydrogen diffusion behavior in the PVA (polyvinyl-alcohol) hydrogel had been done to measure diffusion coefficient (Apparent Diffusion Coefficient/ ADC) used as parameter of brain tumor grading. For our study, PVA hydrogel samples were prepared using freezing-thawing method with various concentration and number of freezing-thawing cycles. The ambiguity of brain tumor grading using ADC value, which is formed from Diffusion Weighted-Imaging 1,5 T, could be reduced enough with observing the result of correlation the ADC at b-value 1000 s/mm2 and 3000 s/mm2 with assessment of consistency measured using digital penetrometer based on microcontroller.